(untitled) (Journal of the College of Basic Education, 2023)
The research problem was identified in the following question:- What is the effect of thinking maps in the achievement of biology subject and in the scientific thinking skills of female second-intermediate class students? This research aims to recognize:- 1- The effect of thinking maps in the achievement of Biology subject in female second-intermediate class students. 2- The effect of thinking maps in the scientific thinking skills of female second-intermediate class students in Biology subject. To be sure of achieving the goals of the research, the following two zero hypotheses have been formulated: 1- There is no statistically significant difference at the level of (0.05) between the average scores of the experimental group students who have studied by thinking maps to that of the average score of the control group students who have studied by usual method in achievement test. 2- There is no statistically significant difference at the level of (0.05) between the average scores of the experimental group students who have studied by thinking maps to that of the average score of the control group students who have studied by usual method in skills of scientific thinking test. The research was applied on the second-intermediate class students in Al-Sana’a secondary school for girls in the Directorate of Education of Baghdad / second Rusafa selected on purpose to represent a field of experience, and the research sample consisted of 53 students, and by random selection , Division (c) was selected as the experimental group, who studied by maps thinking, and consisted of (26) student, and Division (b) the control group, who studied the usual method, and consisted of (27) students The two groups have been equalized in the variables of (chronological age, intelligence, scores of first-intermediate class in Science, test of the previous information in Science and test of skills of scientific thinking), The researcher prepared teaching plans for the two groups of the research, depending on thinking maps and the ordinary method. A map for achievement test was made by which paragraphs of the test were prepared according to four levels: Bloom’s Taxonomy of a (remembering, comprehension, application and analysis), it consisted of (50) subjective paragraph of the multiple-choice type with four alternatives. To check the stability of the paragraphs of achievement test, it has been shown to a group of experts and endorsed the content using skills thinking maps test, it has been applied to two exploratory samples, one for the purpose of knowing the stability and safety of the paragraphs of the test and the time of answering and the other: for the purpose of analyzing the test statistically by extracting the coefficient of difficulty and the distinctive power as well as the effectiveness of wrong alternatives also extracting the test stability (equivalent Kuder Richardson 20), the stability coefficient found equal to( 0.92). The researcher adopted the test of scientific thinking skills, including (30) skills test paragraphs of (observation, classification, interpretation, prediction and generalization) of the multiple-choice type, and for investigating the veracity of its paragraphs (virtual), it has been presented to a group of experts, the skills of scientific thinking were applied before the beginning of the experiment on the students groups, and after completing the experiment, the achievement test was applied on the students of the two groups, and application of skills of scientific thinking of the two groups was repeated . The results showed the superiority of the experimental group students over the control group in both, the achievement test & the test of scientific thinking. In light of the results, the researcher concluded a positive effect of thinking maps in the achievement and the scientific thinking skills of female second- intermediate class students in the subject of Biology, and a set of recommendations and proposals were reached, the most important that the researcher recommends the adoption of thinking maps in the teaching of Biology, and the researcher suggests conducting other studies for several stages and in other subjects.